Profiling of Metabolome in the Plasma Following a circH19 Knockdown Intervention in Diet-Induced Obese Mice - Hanxin Zhao; Dike Shi; Weiwei Gui; Xihua Lin; Jionghuang Chen; Weihua Yu (Metabolites)
The circular RNA circH19 has been implicated in the regulation of gene expression and various biological processes, including obesity. Objectives: This study aimed to elucidate the metabolic changes in plasma after circH19 knockdown in a diet-induced obese (DIO) mouse model. Methods: Plasma samples were collected following the intervention and subjected to non-targeted metabolomics analysis using liquid chromatography–mass spectrometry (LC-MS). Metabolic profiling was performed to identify and quantify metabolites, followed by multivariate statistical analysis to discern differential metabolic signatures. Results: A total of 1250 features were quantified, resulting in the upregulation of 564 metabolites and the downregulation of 686 metabolites in the circH19 knockdown group compared to the control mice. Metabolic pathway analysis revealed disruptions in lipid metabolism, amino acid turnover, and energy production pathways. Notably, the intervention led to a substantial decrease in circulating lipids and alterations in the plasma amino acid profile, indicative of an impact on protein catabolism and anabolic processes. The observed shifts in lipid and amino acid metabolism suggest potential therapeutic avenues for obesity and related metabolic disorders. Conclusions: The circH19 knockdown in DIO mice led to significant alterations in plasma metabolites, highlighting its potential role in the regulation of obesity and metabolic disorders.